Efficacy of Starfruit Leaf Ethanol Extract Gel on Second-Degree Burns in Wistar Rats - Pancarani, Amalia Rizky; Fadhilah, Arini (Indonesian Journal of Pharmacy and Natural Product, 2025)
Burn injuries are injures caused by heat, electricity, chemicals, or radiation exposure. Secondary metabolites found in starfruit (Averrhoa carambola) leaves—such as saponins, alkaloids, and flavonoids—have the potential to accelerate the healing of burn wounds. The main objective of this research is to evaluate the effects of a topical gel made from ethanol extract of starfruit leaves at concentrations of 5%, 10%, and 15%, and to determine the most effective concentration for burn wound healing. This study used an experimental method involving 25 Wistar rats, divided into 5 groups. The burn wound model was created by inducing second-degree burns on the rats' backs using a metal disc with a diameter of 2 cm, applied to the skin for 5 seconds. After the burn was induced, the gel was applied topically twice a day for 15 consecutive days. The healing process was observed macroscopically by measuring the percentage of wound closure and using a modified Nagaoka scoring system. The data obtained from this study showed that the ethanol extract gel of starfruit leaves effectively accelerated the healing of second-degree burns. Tukey's test results indicated that the 15% concentration of the gel produced a statistically significant effect compared to the negative control group (p = 0.012), and was identified as the most effective treatment group, with a burn wound healing percentage of 86.15±0.90%, which was noticeably higher than that of the other groups. Based on analysis using wound healing percentage and Nagaoka scores, the optimal concentration was 15% with healing time equivalent to the positive control group.